A High-Resolution MRI Study of Relationship between Remodeling Patterns and Ischemic Stroke in Patients with Atherosclerotic Middle Cerebral Artery Stenosis - Zhang, Dan-Feng; Chen, Yu-Chen; Chen, Huiyou; Zhang, Wei-Dong; Sun, Jun; Mao, Cun-Nan; Su, Wen; Wang, Peng; Yin, Xindao (Frontiers in Aging Neuroscience, 2017)
Purpose: Recently, high-resolution magnetic resonance imaging (HR-MRI) has been used to depict the wall characteristics of the intracranial arteries. The aim of this study was to explain the relationship between the remodeling patterns and acute ischemic stroke in patients with atherosclerotic middle cerebral artery (MCA) stenosis using HR-MRI. Material and methods: From August 2015 to May 2016, we prospectively screened 33 consecutive patients with unilateral MCA stenosis using time-to-flight (TOF) MR angiography, including 15 patients with symptomatic MCA stenosis and 18 patients with asymptomatic MCA stenosis. Among them, 14 patients were diagnosed as positive remodeling (PR) and 19 as negative remodeling or non-remodeling. The cross-sectional images of the stenotic MCA wall on HR-MRI including T1WI, T2WI, and PDWI were compared between the symptomatic group and the asymptomatic group as well as the PR group and the non-PR group, based on the vessel area, lumen area, wall area, plaque area, degree of stenosis, remodeling index, and NIHSS score. Results: The symptomatic group had larger wall area (P=0.040), plaque area (P<0.001), degree of stenosis (P=0.038), remodeling index (P<0.001), and NIHSS score (P=0.003) as well as smaller lumen area (P=0.001) than the asymptomatic group. In addition, more PR patients were observed in symptomatic group. The PR group had larger plaque area (P=0.014) and NIHSS score (P=0.037) than the non-PR group. Demographic and clinical characteristics between the symptomatic group and the asymptomatic group, the PR group and the non-PR group showed no statistical difference. Conclusions: The current study suggests that the HR-MRI has emerged as a promising tool to detect the characteristics of intracranial arteries wall and reveal the relationship between remodeling patterns and ischemic stroke. The PR is an unsafe remodeling way and is prone to cause acute ischemic stroke.